Introduction to system dynamic modelling and vensim software - Sapiri, Hasimah; Zulkepli Hew, Jafri; Ahmad, Norazura; Zainal Abidin, Norhaslinda; Hawari, Nurul Nazihah (UUM Press, 2017)
System dynamics simulation modelling technique is taught to students at undergraduate and graduate levels.The students are taught how to develop a system dynamics model of the system under study. This book is written to help students understand the concepts and fundamental elements of system dynamics simulation, and provide a step-by-step guide in conducting a system dynamics study. This book is suitable for students who are studying system dynamics simulation modelling at undergraduate and graduate levels.It offers the concepts and application of system dynamics as well as provides an approach for modelling effectively.Having read this book, the reader will be able to: ·Learn the concept of system dynamics simulation and its application, Understand the important steps of modelling process, and·Conduct a system dynamics study successfully.